Isolation, Identification, Morphological Studies and Lipid Granules Staining (Nile red) of Different Micro-Algae for Biodiesel Production from Fresh Water and Saline Water - Santhose, P. Arul Murugan, S. Elumalai*, R. Sakthivel, B. Infant (Journal of Experimental Sciences, 2011)
In the present study, the algal samples were collected from temple tanks, saline water in Chennai, Mahapaliburam and Kovallam. Collections were carried out during the month of September 2010 and February 2011. Samples were studied in the laboratory and identified. In their surveyed the population, identification, morphological, and examined the Nile red method with microalgae genus of various classes. Various physical and chemical treatments were applied to the existing Nile red method to improve the effectiveness and efficiency. The following algae were present Chlorella vulgaris, Nannnochloropsis, Dunaliella tertiolecta, Tetraselmis suecica, Chlorococcum humicolo, Scenedesmus acuminatus, Amphora coffeaformis, and Nitzschia longissima. Algae are described with photographs.